Cultural Diplomacy of Ukraine in Conditions of the Russian-Ukrainian War - Svetlana Klavdienko (Language, Culture, Politics)
The article studies the peculiarities of the development of cultural diplomacy of Ukraine in the conditions of war. For a long time, cultural diplomacy of Ukraine developed unsystematically. The importance of increasing attention to cultural diplomacy during the war is emphasized. Cultural diplomacy forms a platform for interaction between different cultures and aims at mutual understanding, tolerance, and collaboration between states. The main goal of Ukraine's cultural diplomacy in the conditions of the Russian-Ukrainian war is to strengthen subjectivity, to form a positive image of the country. Convincing examples of cultural diplomacy during the war are considered. The SWOT analysis of the cultural diplomacy model of Ukraine is carried out. The strong points and ways of neutralizing the weaknesses of cultural diplomacy are defined. A number of problems it currently faces are analysed. The importance of a clear strategic approach of the state to the development of cultural diplomacy is emphasized.